Evaluation of Capacity and Parking Needs in Apartment Buildings Case Study of Apartment Tokyo Riverside PIK 2 - Suhardja, Iwan; Bonifacius, Nurhamdoko; Budiyanto, Hery (Proceedings of International Conference of Graduate School on Sustainability, 2025)
Parking is one of the infrastructures that cannot be separated from the transportation system. The design of a proper parking system is crucial in the construction of a building to prevent future parking problems. The existence of infrastructure such as parking facilities is very much needed, one of which is in the building area, or in this study, is an apartment. Tokyo Riverside Apartment PIK 2 North Jakarta is an apartment designed as a residence and office located in Kamal Muara, Penjaringan District, North Jakarta City, Special Capital Region of Jakarta 14470. During the construction of this apartment, careful consideration is given to parking management, ensuring a balance between the need for parking space and the number of existing vehicles. Evaluation of parking space needs planning will discuss parking characteristics, parking space needs (KRP), and Apartment KRP standards. The method used in this study is to conduct a survey of vehicle entry and exit at the comparison building, then calculate the number of parking spaces available at the study building and evaluate the need for parking space against the comparison building and the 1996 Directorate General of Land Transportation parking manual, then determine the design of vehicle circulation in and out, then draw conclusions and suggestions. Based on the results of this study, the minimum Parking Space Requirement that must be provided by the developer is 183 m2/SRP, which is 323 SRP. The Parking Space Requirement planned by the architect or developer is 1454 SRP, so the Parking Space Requirement provided by the developer is sufficient. Technical planning for vehicle circulation in and out is carried out through the south side of the apartment using a one-lane system.